Charakterystyka nieformalnego rynku venture capital w Polsce i innych krajach europejskich - Waniak-Michalak, Halina (Characteristic of Polish and European Informal Venture Capital Market, 2007)
The supply of start-up and early-stage equity finance has become more and more dependent on business angels, as venture capital funds are not able to accommodate a large number of small deals with heavy due diligence requirements. Recognition of the importance of business angels and angel networks at public policy level is needed to create an environment favoring their investments. The aim of this article is to characterize the market, to put in order all the most important information of the informal market in Poland and in Europe. The conclusions and the data are to be the introduction to further discussion, publications and researches.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 609-616